Diphtheria outbreak in Yemen: the impact of conflict on a fragile health system - Dureab, Fekri; Al-Sakkaf, Maysoon; Ismail, Osan; Kuunibe, Naasegnibe; Krisam, Johannes; Müller, Olaf; Jahn, Albrecht (Conflict and health, 2019)
War in Yemen started three years ago, and continues unabated with a steadily rising number of direct and indirect victims thus leaving the majority of Yemen’s population in dire need of humanitarian assistance. The conflict adversely affects basic socioeconomic and health conditions across the country.